An estimation of the Seychelles CO2 footprint using Eurostat data - Patrice Guillotreau; Kevin Bistoquet (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2022)
Small island developing states (SIDS) are particularly vulnerable to climate change and ought to pay attention to their own contribution in the form of carbon dioxide (CO2) emissions resulting from domestic production and consumption levels. Although barely responsible for worldwide carbon emissions by way of the modest level of their domestic demand, they can nonetheless contribute to the problem because of global demand for their exported commodities. However, the CO2 footprint of SIDS is rarely assessed because of a lack of data about greenhouse gas emissions or national account statistics. Taking the opportunity of the COVID-19 pandemic and the resulting economic shock, an environmentally-extended input-output model based on Eurostat data on air emissions is used to disentangle CO2 emissions embodied in domestic production and international trade, and to identify clearly the origin of emissions by industry. Not surprisingly, the consumption-based CO2 footprint of Seychelles is deemed lower (6.79 tonnes of CO2 per inhabitant) than the production-based inventory (9.55 tonnes of CO2 per inhabitant) for this small open economy relying to a large extent on exports of canned tuna and tourism services. Hence CO2 emissions decreased (- 16 %) in 2020 because of the COVID-19 pandemic. Could it be the right time to re-frame the international specialisation of Seychelles?
Keywords: D57; N57; Q25; 330; environmentally-extended input-output (EE-IO) model; air emission accounts; CO2 footprint; COVID-19; Seychelles economy